Designing at the Edge: Critical Food Futures, Posthuman Ethics, and the Politics of Taste - Simões, José; Bonacho, Ricardo (Design/Arts/Culture, 2026)
This article examines how contemporary food design practices, spanning from speculative artefacts to commercial innovations, balance the tensions between nature and technology, authenticity and simulation, critique and scalability. Through a comparative analysis of four case studies (The Sausage of the Future, Edible Growth, Perfect Day, and NotCo), we explore how food design shapes the ethical, sensory, and systemic dimensions of food. Drawing on critical design theory, posthumanist thought, and decolonial perspectives, the study challenges the dominance of techno-scientific narratives and advocates for more inclusive, culturally grounded, and multispecies approaches to food futures. We propose a typology based on two key dimensions - symbolic depth and systemic traction - to assess how food artefacts mediate cultural meaning and infrastructural change. This framework invites a shift from novelty-driven food design to practices rooted in ethics, care, and epistemic diversity.